EDUCAÇÃO-AMBIENTAL NA PRODUÇÃO DE DIFERENÇAS EM PROCESSOS CRIATIVOS DA DOCÊNCIA-AMBIENTAL - Almeida, Denize Mezadri de (2020)
It is a qualitative research with the thesis that meetings of teaching collectives in their existential spaces, produce creative and inventive differentiations (MATURANA; VARELA, 1995; DELEUZE; GUATTARI, 1995) of teaching-environment. For this purpose, it